2016
DOI: 10.1111/jgs.14447
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Social Participation and 3‐Year Change in Instrumental Activities of Daily Living in Community‐Dwelling Elderly Adults

Abstract: OBJECTIVES:To investigate whether social participation (SP) in older adults is associated with ability to perform instrumental activities of daily living (IADLs). DESIGN: Prospective cohort study. SETTING: Two local municipalities of Nara, Japan. PARTICIPANTS: Individuals aged 65 to 96 (n = 2,774 male, n = 3,586 female) free of IADL disability at baseline. MEASUREMENTS: SP and IADLs were assessed using self-administered questionnaires. SP was categorized into five types and assessed using the number and type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
91
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 96 publications
(110 citation statements)
references
References 43 publications
(91 reference statements)
11
91
1
1
Order By: Relevance
“…Based on prior studies [49, 14, 15, 2325], the following variables were used as covariates that may mediate the association between SP and IADL: age, residential area, marital status, subjective economic situations, pensions, chronic diseases, body mass index (BMI), alcohol, smoking, dietary habit, depression, cognitive function, self-rated health, and having a purpose in life. Data on age and residential areas were provided by city governments, and data for other covariates were procured from the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on prior studies [49, 14, 15, 2325], the following variables were used as covariates that may mediate the association between SP and IADL: age, residential area, marital status, subjective economic situations, pensions, chronic diseases, body mass index (BMI), alcohol, smoking, dietary habit, depression, cognitive function, self-rated health, and having a purpose in life. Data on age and residential areas were provided by city governments, and data for other covariates were procured from the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Because it’s noted that there are gender differences in IADL difficulties among older adults [13], it is necessary to examine male and female IADL separately when viewing it as a health outcome. Since there are limited numbers of studies regarding the association between SP and IADL, we examined the types of social activities which community dwelling elderly people participate in as well as the impact of SP on IADL with specific attention given to gender difference [14, 15]. Their results were as follows; a prospective cohort study [14] revealed that among females, participation in volunteer groups, hobby groups, senior citizen clubs, and local events was associated with decreased risk of IADL decline, whereas among males, only participation in hobby groups was protective for IADL decline.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations